Empowering nonprofits in the digital age: a strategic playbook for online marketing - Low, Alexa, author (Colorado State University. Libraries, 2024)
In today’s digital world, honing effective marketing strategies are critical for all varieties of organizations, yet community-based nonprofits often must overcome additional challenges due to limited resources and funds. Within this thesis I will explore how nonprofit organizations can implement effective digital marketing practices to promote their missions, grow community connections, and achieve their initiatives. Building on my volunteer experience with the Redwood Heights Association (RHA), a community-based nonprofit out of Oakland, California, I created a strategic digital marketing playbook suited to the needs and characteristics of nonprofit organizations. This nonprofit playbook focuses on four main areas: social media strategies, Google marketing tools, online accessibility, and practical planning/management resources. Through leveraging resources such as Google Ads, Canva, Meta Business Suite, and WordPress, I developed recommendations to structure content creation, enhance online reach, and invoke community engagement. Focusing on inclusivity, my thesis discusses the importance of digital accessibility for all users, aligning with compliance standards to measure these requirements. Intermixing my experience with RHA and my marketing knowledge, my thesis provides a structured guide for nonprofits navigating the digital world through actionable recommendations and substantial tools.
Keywords: marketing; digital marketing; nonprofits